Improving Learning Outcomes in Thematic Learning Through Audio Visual Media for Third Grade Students of SDN Kauman 01 - Pangrango i Niken Prastiwi (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
This reseach entitled "Improving learning outcomes in thematic learning through audio-visual media for third grade students of SDN Kauman 01". The purpose of this study was to improve student learning outcomes through audio-visual media. This research uses Classroom Action Research (PTK). The subjects of this study were third grade students of SD Negeri Kauman 01 Batang in the first semester of the 2020/2021 school year. The success of this study was observed based on the percentage of completeness of student learning outcomes obtained from the evaluation test scores at the end of each cycle. Students are declared complete learning when they reach a value of 70 and one class is declared complete learning if they have reached a percentage of 85% of students who have scored 70 or more. After carrying out classroom action research, it was concluded that audio-visual media can improve student learning outcomes in class III thematic learning